Numerical prediction and experimental validation of free vibration responses of hybrid composite (Glass/Carbon/Kevlar) curved panel structure. (1st June 2020) - Sahu, Pruthwiraj; Sharma, Nitin; Panda, Subrata Kumar
Abstract: This research reveals the effect of hybridisation numerically for different advanced fibre (Glass/Carbon/Kevlar) reinforcement in polymer matrix composite on the eigen-characteristics. The higher-order displacement polynomial kinematics and curvature effect have been utilized for the modelling of the hybrid composite component including the necessary shear deformation. The adequate solution accuracy of the derived hybrid composite mathematical formulation has been examined by comparing with the first-five modal data considering the effect of aspect ratios, numbers of layers and the fibre types with the experimental data. The eigen-frequency solutions are obtained using an isoparametric linear finite element formulation in association with experimental properties for the hybrid composite. Also, the modal responses are obtained via a simulation model considering the individual layer effects of each fibre through the static-structural module of the commercial package (ANSYS). Finally, the influential structural design parameters (thickness ratio and constraint conditions) affecting the frequency characteristics including the geometrical shape are examined using the present numerical model. The computational results reveal that the numbers of layer and type of fibre affect the frequency parameter due to the variation in their stiffness.